Transient reactivation of small ensembles of adult-born neurons during REM sleep supports memory consolidation in mice - Sakthivel Srinivasan; Iyo Koyanagi; Pablo Vergara; Yuteng Wang; Akinobu Ohba; Toshie Naoi; Kaspar E. Vogt; Yoan Chérasse; Noriki Kutsumura; Takeshi Sakurai; Taro Tezuka; Masanori Sakaguchi (Nature Communications)
Abstract While memory consolidation is widely believed to require memory reactivation synchronized with theta oscillations during REM sleep, direct causal evidence linking specific neuronal ensembles to this process has been lacking. Strong theta oscillations arise in the hippocampal dentate gyrus, where a small population of principal neurons is continuously generated throughout adulthood. Although these adult-born neurons (ABNs) are known to modulate hippocampal circuits for memory, the causality between their specific information content and memory-related behavior was unknown. Here, we show that REM sleep reactivation of memory ensembles comprising as few as ~3 ABNs is necessary for fear memory consolidation. Crucially, we found that the synchronization of ABN activity with a specific theta phase is essential for associative memory consolidation. Our findings thus provide causal evidence that consolidation critically depends on both the reactivation of minimal neuronal populations and precise neuronal coordination within theta-defined temporal windows.